INTEGRATED MANAGEMENT OF CITARUM RIVER BASIN: A CASE STUDY TOWARD SUSTAINABLE DEVELOPMENT AND COMMUNITY PARTICIPATION - Tjokrokusumo, Sabaruddin Wagiman (Jurnal Hidrosfir Indonesia, 2006)
Water quantity is perceived as a problem to meet increasing demands of present human population for food, drinking, hygiene, and other domestic use and industry. However, quality aspect have also become a growing concern as a result of untreated release of domestic, urban and industrial discharges as well as non pint sources, e.g. agriculture. Citarum river basin is one of the biggest river basins in Indonesia. It covers 608 000 hectares, including 7 regencies and 2 cities (Bandung and Cimahi) in the province of West Java. Its huge source of freshwater have been contaminated from point and non-point sources of pollution, resulting in its very poor quality of very strategic and important source of freshwater in Indonesia for generating electricity, irrigating agricultural land, supplying fresh drinking water, and farming fish and also creating eco-tourisms. In order to protect this important freshwater resource, Agency for the Assessment and Application of Technology (BPP Teknologi) in collaboration with local government of West Java Province implementing environmentally sound technology to manage water quality of Citarum River Basin properly. The objectives of this project are (1) to protect freshwater resource from pollution, (2) to reduce pollution loads from point and non-point sources, (3) to introduce best available management for minimizing pollution, (4) to create sustainable community for best management practices to protect their water front village. Share experiences and exchange information, knowledge, and technology was done through ASEM Water Net to develop international partnership on Integrated River Basin Management.